Utilization of the Casertana pig to obtain traditional, typified labelled salami. II. Qualitative characteristics of meat at carcass jointing - Castellano N.; Colatruglio P.; Barone C.M.A.; Gigante G.; Rossetti C.E.; Zullo A.; Matassino D. (5. International Symposium on the Mediterranean Pig, 2007)
The research was carried out on 15 castrated males and 10 females of the Casertana pig slaughtered at a live weight ranging from 130 kg to 250 kg. Rheological and colorimetric characteristics were determined on the following muscles: caput longum tricipitis brachii (CL), longissimus dorsi (LD), psoas maior (PM), anconeus (PA), supraspinatus (SS) after storing at -20°C for 120±10 days. Data were elaborated by GLM procedure of SAS using live weight as covariate and sex, muscle and their interaction as fixed factors. Results showed that females have darker meat (P<0.01), with a lower value of a* (P<0.001) and a higher value of b* (P<0.001) in comparison with castrated males. LD muscle showed the lowest values of a* and b* and it was characterised by greater lightness, with the lowest chroma and the highest hue values. On the other hand, PA was the darkest muscle and showed the worst rheological traits. PM, which was the most red muscle with the highest b* value, exhibited the lowest hardness and chewiness values. Sex did not significantly affect rheological characteristics.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)